Aetiologic Agents of Fry Mortality Syndrome in the Rainbow Trout (Oncorhynchus Mykiss) in Iran - Jalil Zorriehzahra, Seyed Mohammad Ebrahim (2008)
An investigation was conducted in order to find out the etiological factors of Fry Mortality Syndrome (FMS) that causes serious economical loss in rainbow trout farms in Iran. In recent years obscure fry mortalities have been observed in many hatchery farms in Iran. It was reported that the rate of fry and juvenile mortality increased dramatically in some provinces e.g. 23 million fry were produced in hatchery centers of Chahar Mohal Bakhtiary province in 2002 but nearly 21 million fry (91.3%) in different stages of growth died before distribution to farmers. Also close to 23 million fry were produced in Mazandaran province, but 12 million fry equivalent to 52.12% of total fry production died mysteriously.This investigation was carried out with objectives of detecting and confirming the main causative agent that contribute to the occurrence of Fry Mortality Syndrome in Iran. During 32 months, from October of 2001 until May of 2004, 52 different hatchery centers and rearing farms of rainbow trout (Oncorhynchus mykiss) which were located in Tehran, Mazandaran, Guilan, Fras, Markazi, Kerman and Kohkiloyeh Boyerahmad provinces, were visited and various samples from affected farms were collected. Collected samples consisted of ovarian fluid, milts, eggs, eyed-eggs, larvae, fry < 1 g and 1-3 g as well as internal organs from adult fishes. A total of 2,107 samples were collected from farms in six provinces and were examined by five methods such as virology (410 samples), bacteriology (899 samples), serology (consisted of IFAT: 392 samples and ELISA: 44 samples), histopathology (160 samples) and hematology (202 samples). Some of the mentioned approaches such as fish cell culture, ELISA and IFAT techniques were set-up and optimized for the first time in Iran. The clinical signs of suspected fishes were darkening, exophthalmia, ascites, abnormal swimming and whirling. From 410 samples that of tissues inoculated on to cell cultures two samples showed CPE in EPC and BF-2 cell lines which were inoculated with ovarian fluid from broodstock obtained from hatchery farms in Mazandaran province. The CPE was similar to IHN virus induced. The CPE foci revealed dying cells congegrated as grape-like clusters (ballony performance with cytolysis).TEM findings in infected cells showed bullet-shaped particles having sizes of 130-180 nm in length and 65-70 nm in diameter. From the virion morphology it was suggested that observed particles were similar to Rhabdovirus. FAT examination revealed that all samples were examined with MAbs and PAbs against IPNV and VHSV were negative. On the other hand, two samples were positive when examined with MAbs and PAbs against IHNV. These smears were originated from samples that had showed CPE in EPC and BF-2 cell lines and bullet shaped particles in electron microscopy. ELISA findings (cut-off value, optical density and detectionlevel percentage) showed that IHNV had higher percentage of detection with 23.25% in comparison with other relevant viral diseases i.e. IPNV with 7.31% and VHSV with 14.29%. Results of histopathological study on the sampled fry revealed that the target tissues in the kidney, liver, spleen, hepatopancreas, intestine and gills showed different degree of tissue changes beginning from cell degeneration to complete necrosis. There were also renal blood vessels congestion, marked degenerative changes in posterior kidney with tubular necrosis and interstitial hematopoeitic tissue degeneration. In addition, interstitial degeneration and oedema in anterior portion of kidney, focal necrosis in the tubular area and several stages of cell necrosis in the hematopoeitic tissue were the most important histopathological changes seen in kidney tissues examined. Hepatopancreatic tissues also revealed marked changes such as congestion, atrophy and necrosis of pancreatic acinar cells and Islets of Langerhans. Spleen samples revealed spleenic congestion, severe necrosis, hemosiderosis and increased presence of melanomacrophage centers (MMC). Gills tissue in sampled fry showed hyperplasia, clubbing and fusion of lamellae. Hematological findings revealed that total white blood cell count, i.e. lymphocyte and neutrophil in investigated fish showed significant increased compared with the control fish (p< 0.05). On the contrary, all the samples showed a decreased in RBC, Hb and HCT values. In addition, MCHC and total protein plasma showed a marked decreased (p<0.05). In the blood serum components analysis, similarly it was revealed LDH and AST showed a significant decreased (p<0.05). In conclusion, with marked clinical signs, cell culture observation and TEM findings, ELISA and IFAT results, histopathology and hematological findings (blood and biochemical parameters) seen in the current investigation lead to possibility of a viral disease agent infection as the cause of fry mortality syndrome in the hatchery and rearing trout farms in Iran. From findings of the current study, it is concluded that IHN-like virus could be most probable etiologic of fry mortality syndrome in Iran. Key words: Fry Mortality Syndrome, Rainbow trout, Cell culture, TEM, ELISA, IFAT, Histopathology, Hematology, IHNV, IPNV, VHSV, Iran